Duration of Venoarterial Extracorporeal Membrane Oxygenation and Mortality in Postcardiotomy Cardiogenic Shock - Mariscalco, Giovanni; El-Dean, Zein; Yusuff, Hakeem; Fux, Thomas; Dell'Aquila, Angelo M; Jónsson, Kristján; Ragnarsson, Sigurdur; Fiore, Antonio; Dalén, Magnus; di Perna, Dario; Gatti, Giuseppe; Juvonen, Tatu; et al. (Journal of cardiothoracic and vascular anesthesia, 2021)
OBJECTIVE: The optimal duration of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in patients affected by postcardiotomy cardiogenic shock (PCS) remains controversial. The present study was conducted to investigate the effect of VA-ECMO duration on hospital outcomes. DESIGN: Retrospective analysis of an international registry. SETTING: Multicenter study including 19 tertiary university hospitals. PARTICIPANTS: Between January 2010 and March 2018, data on PCS patients receiving VA-ECMO were retrieved from the multicenter PC-ECMO registry. INTERVENTIONS: Patients were stratified according to the following different durations of VA-ECMO therapy: ≤three days, four-to-seven days, eight-to-ten days, and >ten days. MEASUREMENTS AND MAIN RESULTS: A total of 725 patients, with a mean age of 62.9 ± 12.9 years, were included. The mean duration of VA-ECMO was 7.1 ± 6.3 days (range 0-39 d), and 39.4% of patients were supported for ≤three days, 29.1% for four-seven days, 15.3% for eight-ten days, and finally 20.7% for >ten days. A total of 391 (53.9%) patients were weaned from VA-ECMO successfully; however, 134 (34.3%) of those patients died before discharge. Multivariate logistic regression showed that prolonged duration of VA-ECMO therapy (four-seven days: adjusted rate 53.6%, odds ratio [OR] 0.28, 95% confidence interval [CI] 0.18-0.44; eight-ten days: adjusted rate 61.3%, OR 0.51, 95% CI 0.29-0.87; and >ten days: adjusted rate 59.3%, OR 0.49, 95% CI 0.31-0.81) was associated with lower risk of mortality compared with VA-ECMO lasting ≤three days (adjusted rate 78.3%). Patients requiring VA-ECMO therapy for eight-ten days (OR 1.96, 95% CI 1.15-3.33) and >10 days (OR 1.85, 95% CI 1.14-3.02) had significantly greater mortality compared with those on VA-ECMO for 4 to 7 days. CONCLUSIONS: PCS patients weaned from VA-ECMO after four-seven days of support had significantly less mortality compared with those with shorter or longer mechanical support.
Keywords: centra terciární péče; Humans; lidé středního věku; mimotělní membránová oxygenace; Shock, Cardiogenic; Aged; senioři; lidé; kardiogenní šok; mortalita v nemocnicích; duration; survival; Extracorporeal Membrane Oxygenation; extracorporeal membrane oxygenation; Middle Aged; Retrospective Studies; ECMO; Tertiary Care Centers; retrospektivní studie; Hospital Mortality; cardiac surgery